Do Enterprise Risk Management Disclosure and Intellectual Capital Disclosure Contribute to Firm Value? - Ari Purwati; Abdul Tahir (CV. Sakura Digital Nusantara, 2023)
This study aims to determine the effect on the value of mining companies listed on the Indonesia Stock Exchange (IDX) from the aspect of disclosure of enterprise risk management and disclosure of intellectual capital. The variables that are the focus of this study are the disclosure of enterprise risk management (X1) and intellectual capital disclosure (X2), which are measured using the enterprise risk management disclosure index and intellectual capital disclosure index. Meanwhile, firm value (Y), which is measured using Tobin's Q, acts as the dependent variable in this analysis. The sample of this study was selected through purposive sampling technique, so that there were 32 mining companies that became the sample of the study. The data used in this study were obtained through data collection techniques in the form of documentation. Then, this data is analyzed using data analysis techniques which include classical assumption tests, multiple linear regression tests, and hypothesis testing. The results showed that individually, the disclosure of enterprise risk management practices has a negative impact on firm value, while the disclosure of intellectual capital has a positive impact on the value of mining companies listed on the Indonesia Stock Exchange in 2022. Together, the disclosure of enterprise risk management practices and the disclosure of intellectual capital have a positive impact on the value of the same company in the same year.